Can criminology sway the public? How empirical findings about deterrence affect public punishment preferences - Brendan Rose; Malouke Esra Kuiper; Chris Reinders Folmer; Benjamin van Rooij (Crime Science)
Abstract Background setting Punitive approaches to deter offending remain popular despite limited evidence of their effectiveness. This study investigated what effect presenting empirical criminological findings about the effectiveness of deterrence to a general public has on their punishment preferences. It builds on earlier research showing that such presentation reduces the public’s inclination towards strict punishment. The present study extended this research by exploring whether the impact of scientific evidence on public punishment preferences is affected by crime severity and by exploring cognitive and psychological factors that may underpin this relationship. Methods Using a vignette study paradigm, a general public sample of 330 participants were asked to make hypothetical punishment decisions to reduce crime (whether or not to double sentences) for one of three crime types that varied in severity. For each crime type, half of participants were additionally provided with a summary of research on the deterrent effect of punitive policy measures. Results Presenting scientific evidence reduced participants' preferences for stronger punishment and that this effect remained consistent regardless of crime severity—ranging from burglary to homicide. In addition, we did not find evidence that difference in individuals’ cognitive style, negative emotional reactions, perceptions about seriousness, or beliefs about redeemability moderated or mediated this relationship. Conclusions This study provides compelling findings that further clarify the circumstances required for scientific evidence to be successfully disseminated to a general public to bring their punishment preferences more in line with the state of empirical science.